Solvability and optimal control of fractional differential hemivariational inequalities. (2nd November 2021) - Xue, Guangming; Lin, Funing; Qin, Bin
ABSTRACT: This paper investigates the solvability and the optimal control of fractional differential hemivariational inequalities (FDHVIs, for short). Firstly, we establish several sufficient assumptions for FDHVIs to transform the solution mappings into differential inclusions. Then, we verify the non-emptiness and the compactness of the set of all the mild solutions for FDHVIs. Furthermore, we discuss the optimal control problems of FDHVIs via some appropriate hypotheses. Finally, a typical example is presented to illustrate our main results.